2019
DOI: 10.1016/j.ymgmr.2019.100496
|View full text |Cite
|
Sign up to set email alerts
|

Open-label clinical trial of bezafibrate treatment in patients with fatty acid oxidation disorders in Japan; 2nd report QOL survey

Abstract: Introduction Fatty acid oxidation disorders (FAODs) are rare diseases caused by a defective mitochondrial fatty acid oxidation (FAO) enzyme. We recently reported that bezafibrate improved patient quality of life (QOL) based on the SF-36 questionnaire score in patients with FAODs during a 50-week, open-label, clinical trial. Herein we conducted further survey assessments of the trial patients to define the long-term efficacy and safety of bezafibrate. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…MtDNA copy number, indicative of the amount of mitochondria present within the cell, was also increased in bezafibrate treated cells [133]. Interestingly, a follow-up study of patients with VLCAD or CPT II deficiencies treated with bezafibrate resulted in improved quality of life as well as increased physical functioning, confirming bezafibrate's therapeutic potential [136].…”
Section: Treatment Of Mitochondrial Disease and Echs1dmentioning
confidence: 84%
See 1 more Smart Citation
“…MtDNA copy number, indicative of the amount of mitochondria present within the cell, was also increased in bezafibrate treated cells [133]. Interestingly, a follow-up study of patients with VLCAD or CPT II deficiencies treated with bezafibrate resulted in improved quality of life as well as increased physical functioning, confirming bezafibrate's therapeutic potential [136].…”
Section: Treatment Of Mitochondrial Disease and Echs1dmentioning
confidence: 84%
“…An initial trial of patients with CTP II and VLCAD deficiencies found that bezafibrate was unable to improve symptoms or FAO function during exercise, suggesting that previous in vitro findings would not translate to a clinical setting . However, more recent in vitro and in vivo studies have shown greater therapeutic potential . Bezafibrate treatment increased PGC‐1α expression in human induced pluripotent stem cells, resulting in increased cell number and SDHA (OXPHOS complex II subunit) and COX‐1 (OXPHOS complex IV subunit) levels .…”
Section: Treatment Of Mitochondrial Disease and Echs1dmentioning
confidence: 99%
“…Further studies performed preferentially in vivo in animal models and in patients affected by FAOD are therefore necessary to further clarify the underlying mechanisms of tissue damage in these disorders. Finally, it is expected that, besides restricting fat dietary intake and avoiding fasting, drugs that stimulate mitochondrial function such as bezafibrate and the anaplerotic compound triheptanoin may hopefully improve the clinical outcome of the affected patients (Gillingham et al, 2017;Vockley et al, 2017Vockley et al, , 2019Yamada et al, 2018;Shiraishi et al, 2019;Suyama et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…L-Carnitine supplementation should be used mainly to correct L-carnitine deficiency, but its beneficial effect to significantly increase the urinary excretion of potentially toxic fatty acids has still to be demonstrated (Spiekerkoetter et al, 2009. More recently, clinical trials have shown that bezafibrate, an agonist of peroxisome-proliferating activator receptor that increases mitochondrial biogenesis and the gene expression of mitochondrial fatty acid oxidation enzymes, may be useful in VLCAD (Yamada et al, 2018;Shiraishi et al, 2019) and MTP (Suyama et al, 2020) deficiencies. However, the clinical efficacy of bezafibrate is still disputed and needs to be further confirmed (Ørngreen et al, 2014, 2015).…”
mentioning
confidence: 99%
“…Bezafibrate which is a peroxisome proliferator activated receptor agonist that decreases human serum lipid levels has been recently reported to be a promoting drug for fatty acid oxidation disorders based on enhanced transcription β-oxidation enzymes. Clinical trials have reported improvements in some quality of life components [10].…”
Section: Fasteninduzierte Rhabdomyolyse Bei Einem Jugendlichen Mädchenmentioning
confidence: 99%